Structure–Performance Relationship for Dialkyldimethoxysilane as an External Donor in Stopped‐Flow Propylene Polymerization Using a Ziegler–Natta Catalyst. Issue 18 (10th June 2014) - Poonpong, Supawadee; Dwivedi, Sumant; Taniike, Toshiaki; Terano, Minoru; Sun, Wen‐Hua
<x xml:space="preserve">Abstract</x> The structure–performance relationship for dialkyldimethoxysilane external donors is studied at the level of active sites by stopped‐flow propylene polymerization combined with temperature rising elution fractionation (TREF) and density functional theory calculations. The impact of the molecular structure of various dialkyldimethoxysilanes on the catalyst activity and polymer stereoregularity is investigated. It is revealed that the bulkiness of the hydrocarbon groups cannot simply explain the obtained performance. The conformation detail of the hydrocarbon groups around the active sites is important. Dicyclopentyldimethoxysilane gives the highest catalyst activity and stereospecificity, based on strong adsorption on the MgCl2 surface and a sterically hindering conformation of dicylopentyl groups around the active sites, respectively. The way of the contact between the alkoxysilane and the catalyst does not affect the kind of newly formed isospecific sites, rather it affects the efficiency of their formation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>